Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/vetsci9100537
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasites Infecting Domestic Animals and Spectacled Bears (Tremarctos ornatus) in the Rural High Mountains of Colombia

Abstract: This research described the co-infection prevalence of endoparasites in Tremartus ornatus and domestic animals in the rural high mountains of Colombia by copro-parasitological examination. Some parasites have a zoonotic potential in wild endangered species and domestic animals in Colombian regions. T. ornatus had a notable infection with Eimeria spp., Ascaris spp., Ancylostoma spp., and Baylisascaris spp. Cryptosporidium spp., Balantidium coli, Anoplocephala spp., and Acanthamoeba spp. In B. taurus, Eimeria sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…Cryptosporidium spp., Ascaris spp., and Baylisascaris spp. had the highest prevalence in our study, similar to findings in wild Andean bears in Peru (Figueroa 2015) and Colombia (Zárate-Rodriguez et al 2022). We report for the first time Trichomonas spp., Coccidia, and Microsporidia in wild Andean bears.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Cryptosporidium spp., Ascaris spp., and Baylisascaris spp. had the highest prevalence in our study, similar to findings in wild Andean bears in Peru (Figueroa 2015) and Colombia (Zárate-Rodriguez et al 2022). We report for the first time Trichomonas spp., Coccidia, and Microsporidia in wild Andean bears.…”
Section: Discussionsupporting
confidence: 89%
“…Ascaris spp. have been reported in wild Andean bears in the west range of Colombia (Zárate-Rodriguez et al 2022), and we reported the presence of this endoparasite in the east range of Colombia.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations